1998
DOI: 10.1038/sj.onc.1202204
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of Dlk, a novel serine/threonine kinase that is tightly associated with chromatin and phosphorylates core histones

Abstract: We cloned a cDNA coding for a novel serine/threonine kinase, Dlk, a protein of 448 amino acids with a predicted molecular weight of 51.3 kDa. The kinase domain shows 81% amino acid sequence identity to the recently identi®ed DAP kinase (death associated protein kinase) (Deiss et al., Genes & Dev., 9, 15 ± 30, 1995), therefore, the new kinase was called Dlk, for DAP like kinase. Northern analyses revealed a single mRNA species of 1.7 kb which was ubiquitously expressed. However, expression levels varied conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 20 publications
2
114
0
Order By: Relevance
“…Yet, within the DAPk family itself, DRP-1 and ZIP-kinase are also capable of phosphorylating the purified regulatory light chain. 2,3,5,6 In fact, ZIPk phosphorylates the RLC on Thr18 and Ser19 in vivo, leading to membrane protrusions that are reminiscent of those observed with DAPk. 37 In addition, introduction of RLC mutated at Thr18 and Ser19 blocked ZIPk-induced protrusions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Yet, within the DAPk family itself, DRP-1 and ZIP-kinase are also capable of phosphorylating the purified regulatory light chain. 2,3,5,6 In fact, ZIPk phosphorylates the RLC on Thr18 and Ser19 in vivo, leading to membrane protrusions that are reminiscent of those observed with DAPk. 37 In addition, introduction of RLC mutated at Thr18 and Ser19 blocked ZIPk-induced protrusions.…”
Section: Discussionmentioning
confidence: 96%
“…1 It is the prototype for a family of death-inducing kinases, which includes DRP-1 and ZIP-kinase (ZIPk). [2][3][4][5][6] In addition to the conserved catalytic module, DAPk harbors multiple functional domains, including eight ankyrin repeats, a cytoskeletal interacting region, and a C-terminal death domain. 1 DAPk activity is necessary for the induction of cell death by ceramide, matrix detachment, oncogene expression, TNF-a, Fas, TGF-b, and IFN-g, and overexpression leads to pronounced death-associated cellular changes, which include membrane blebbing, cell rounding, and the formation of autophagic vesicles.…”
mentioning
confidence: 99%
“…It displays apoptotic functions which like in the case of DAP-kinase depend on its intrinsic kinase activity. Its rat counterpart was also independently cloned and characterized by Kogel et al (1998). DAP-5 belongs to the extended eIF4G family consisting of the aforementioned eIFGI, and the recently cloned eIF4GII (Gradi et al, 1998), and PAIP (Craig et al, 1998).…”
Section: Conclusion and Prospects For The Futurementioning
confidence: 99%
“…Zipper-interacting protein kinase (ZIP) kinase, also termed death-associated protein kinase like kinase (DLK), was originally identified by two different groups and classified as a subfamily of the death-associated protein kinase (DAPK) [1,2]. ZIP kinase is a serine/threonine-specific protein kinase that contains a high homology to the kinase domain of the DAPK at the Nterminus and leucine zipper domain at the C-terminus [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…ZIP kinase is a serine/threonine-specific protein kinase that contains a high homology to the kinase domain of the DAPK at the Nterminus and leucine zipper domain at the C-terminus [1,2]. Previous studies suggested that ZIP kinase is oligomerized through its C-terminal leucine zipper structure and it has been thought that the oligomerization is critical for the activation of the enzyme [1].…”
Section: Introductionmentioning
confidence: 99%